Frequency of Tahajjud Prayer and Its Impact on Sleep Quality Among Elderly People in Karang Werda, Jember Regency - Sofiana, Kristianningrum Dian; Hamzah, zahreni; Kusumadewi, Jihan Tahira; Rachmawati, Dwita Aryadina; kristianningrum dian (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: The elderly experience a decrease in sleep quality, one of which is becoming easier to wake up at night. This can happen, among others, due to the habit of practicing the tahajjud prayer. The relationship between the frequency of tahajud prayer and sleep quality in the elderly has never been studied before. Objectif: This study aims to explore the relationship between the frequency of Tahajjud prayer and sleep quality among elderly individuals at the Karang Werda Communication Forum in Jember Regency. Method: This type of research is descriptive analytic with a cross-sectional design. Samples were selected using purposive sampling and analyzed using the Spearman Rank Correlation method. Results: A total of 28 elderly people in this study were female (n=23; 82.1%), 60-64 years old (n=13; 46.4%), and not working (n=23; 82.1%). A total of 20 (71.4%) elderly practiced tahajud prayer 6-7 times per week. 16 (57.1%) elderly had good sleep quality based on the result of PSQI. The Spearman correlation coefficient was -0.287 (p = 0.131), indicating no significant relationship. Conclusion: There is no relationship between tahajud prayer frequency and sleep quality in the elderly at Karang Werda Communication Forum of Jember.